Citra Destinasi dan Strategi Pemasaran Destinasi Wisata - Budi Budi (Universitas Bunda Mulia, 2018)
ABSTRACTDestination image is an important factor in tourism marketing. Destination image consists of cognitive, affective and conative dimensions. Understanding formation process of destinations image will help the tourism marketers to build or improve destination image that will facilitate loyal visitors to re-visit or recommend to others. This is quantitative research. Instrument was developed by adopting previous studies but still taking into account its relevance. Questionnaires were distributed through the internet network. Subjects of the study who are not residents of Jakarta, and were at least 17 years old. Determination of sample was using random sampling method. Validity Test, Reliability Test, Signification Test, Determinant Test, and Mediation Test were performed. Results show that cognitive affect affective, cognitive affect conative, cognitive together with affective affect conative. Implication of these findings for tourism marketers is destination image constructed from cognitive into affective then into connative. Then tourism marketers should not only focus to build induces cognitive image but organic image as well.Tourism marketers should aware on general information exists in public communication channels and social media regarding on tourist destination that they 'sell'. These information will form cognitive destination image, then affect feeling and ultimately affect actions that will be done by tourists on that tourism destination.Keywords: destination image, induced, organic, cognitive, affective, conative